Advancements and future directions in the antibacterial wound dressings - A review - ALARÇİN, EMİNE; YAŞAYAN, GÖKÇEN (WILEY, 2021)
Wound repair is a complex process that has not been entirely understood. It can conclude in several irregularities. Hence, designing an appropriate wound dressing that can accelerate the healing period is critical. Infections, a major obstacle to wound repair, cause an elevated inflammatory responses and result in ultimate outcome of incomplete and prolonged wound repair. To overcome these shortcomings, there is a growing requirement for antibacterial wound dressings. Dressings with antibacterial activities and multifunctional behaviors are highly anticipated to avoid the wound infection for successful healing. The aim of this review is not only to concentrate on the importance of antibacterial dressings for wound healing applications but also to discuss recent studies and some future perspectives about antibacterial wound dressings.
Keywords: antibacterial wound dressings; biomaterials; inorganic nanostructures; wound healing; MULTIDRUG-RESISTANT BACTERIA; SOFT-TISSUE INFECTIONS; SILVER NANOPARTICLES; ESSENTIAL OILS; ANTIMICROBIAL PEPTIDES; CARBON NANOTUBE; CHITOSAN; HYDROGEL; NANOFIBERS; SKIN